Effectiveness of Telecardiology and SGLT2 Inhibitors in Reducing Hospitalizations for Heart Failure with Reduced Ejection Fraction: A Systematic Review and Meta-Analysis - Bhindar, Shah Zaib; Sudhir, Priyanka; Tummala, Nikhila; Shaik, Asiya Tasleema; Meka, Lakshmi Malavika Reddy; Nalla, Namratha; EETHA, Sai Rohit Chandra; Singla, Bhavna; Singla, Shivam; Alamin, Eman; Parikh, Jainil P.; Mirza, Muhammad Sohail S. (Cardiology and Cardiovascular Medicine, 2025)
Heart failure due to reduced ejection fraction (HFrEF) continues to be one of the leading causes of hospitalization around the world. In many countries, it continues to be accompanied by high readmission rates, which are proving to be quite challenging with respect to patient outcomes. This systematic review and meta-analysis have been undertaken to assess the combined effects of SGLT2 inhibitors and telecardiology on subsequent rates of hospitalization for patients with HFrEF. A thorough search was performed for studies published from 2015 to 2025, including randomized controlled trials (RCTs), database studies, cohort studies, and others. The forest plot generated from meta-analytic data revealed a pooled effect size of 0.77 (95% CI: 0.55 to 1.00), suggesting a moderate beneficial effect of the intervention in reducing hospitalization rates. However, the heterogeneity was substantial (I² = 90.24%), reflecting considerable variability in study populations, intervention types, and follow-up durations. Subgroup analysis showed differences in effect sizes across study types and patient characteristics, with some studies demonstrating stronger benefits than others. Despite heterogeneity, the consistent direction of effect suggests clinical relevance. Publication bias was assessed using funnel plot symmetry and Egger’s regression test, which suggested a low risk of bias despite minor asymmetry, indicating that the meta-analysis findings are relatively robust. These findings highlight that SGLT2 inhibitors, particularly when supported by telecardiology strategies, can contribute meaningfully to reducing hospital readmissions in HFrEF patients. However, further largescale, standardized trials are needed to clarify the role of telecardiology and optimize its integration into clinical practice. This review supports a combined therapeutic model that incorporates both pharmacological and digital health approaches for improved heart failure management.